2023
DOI: 10.3389/fpls.2023.1080504
|View full text |Cite
|
Sign up to set email alerts
|

Genes related to osmoregulation and antioxidation play important roles in the response of Trollius chinensis seedlings to saline-alkali stress

Abstract: Saline-alkali stress is one of the main abiotic stress factors affecting plant growth and development. Trollius chinensis is a perennial herbal medicinal plant with high values for garden application. However, its response and tolerance to saline-alkali stress is unclear. In this study, we mixed four salts (NaCl: Na2SO4: NaHCO3: Na2CO3) with a concentration ratio of 1:9:9:1, and applied low (40 and 80 mM) and high (120 and 160 mM) saline-alkali stress to analyze osmotic regulation substances, antioxidant syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The transcription factors belonging to the C3H-type zinc finger family are crucial in various aspects of plant growth and development and in their ability to adapt to biotic and abiotic stressors ( Liu et al, 2020 ). FAR1 and NAC transcription factors families are more expressive in plants during stress conditions ( Tran et al, 2007 ; Hou et al, 2023 ). However, Srivastava et al (2018) reported the most significant members of transcription factors TIG (1,241, 10.55%), followed by FAR1 (925, 7.86%), C3H (785, 6.67%), MYB/MYB related (680, 5.78%).…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factors belonging to the C3H-type zinc finger family are crucial in various aspects of plant growth and development and in their ability to adapt to biotic and abiotic stressors ( Liu et al, 2020 ). FAR1 and NAC transcription factors families are more expressive in plants during stress conditions ( Tran et al, 2007 ; Hou et al, 2023 ). However, Srivastava et al (2018) reported the most significant members of transcription factors TIG (1,241, 10.55%), followed by FAR1 (925, 7.86%), C3H (785, 6.67%), MYB/MYB related (680, 5.78%).…”
Section: Discussionmentioning
confidence: 99%
“…In order to maintain their water potential, plants synthesize columns of small molecules to prevent water loss, including Pro, soluble proteins, betaine, and SS [40]. Previous research has illustrated that the SS and Pro concentration in Aquilegia species [17] and Trollius chinensis [54] increased under salt or saline-alkali stress. In this study, the concentration of Pro and SS was found to be elevated in I. typhifolia under artificial saline-alkali stress (T50-T200), which showed that Pro and SS play essential roles in defending against artificial saline-alkali stress.…”
Section: Effects Of Artificial Saline-alkali Stress On the Concentrat...mentioning
confidence: 99%
“…It is essential to recognize that genetic factors play a pivotal role in determining how a plant responds to stressors. Hou et al (2023) reported that genes related to osmoregulation and antioxidation play important roles in the response of Trollius chinensis. Some genotypes may exhibit higher resilience and adaptive capacity, leading to nonsignificant differences at specific doses, while others may be more susceptible, resulting in significant variations in leaf morphology.…”
Section: Morphological Leaf Characteristics Of Pennisetum Purpureum C...mentioning
confidence: 99%